Civil Liability of Hospitals for Tort Law of Swapped Babies: A Comparative Analysis between Indonesia and Malaysia - Sherlyta Ramadhani; Dwi Aryanti Ramadhani (Melayunesia Law, 2025)
This article examines the civil liability of hospitals in cases of swapped babies through a comparative analysis between Indonesia and Malaysia, focusing on the formulation of the elements of unlawful acts and the forms of responsibility of both countries. This issue is important because negligence in infant identification not only causes material and psychological losses but also impacts children's civil rights and reduces public trust in health services. The research method used is normative juridical research with a comparative legal approach. The main findings of this paper indicate that Indonesia assesses cases of swapped babies through the elements of unlawful acts, while Malaysia uses the tort of negligence approach. This difference gives rise to practical liability, where Indonesia tends to emphasize proving the elements of unlawful acts formally, while Malaysia provides broader scope for the standard of care test through jurisprudence. Furthermore, Malaysia has a more varied scope of compensation, while Indonesia limits the form of compensation to material and non-material losses within the limits of propriety. These findings are important for strengthening patient safety standards and hospital accountability mechanisms to be more adaptive to complex immaterial losses. The results of this study can also be used as a guideline for further research.